A systematic literature review on academic title studies in genre analysis - Wang, Zhijie; Abdul Jabar, Mohd Azidan; Mohd Jalis, Farhana Muslim (Sciedu Press, 2024)
This systematic literature review examined the titles of academic texts in the context of genre analysis, an area obtaining increasing academic attention. Employing PRISMA (2020), this study systematically analyzed 52 studies (2004–2024) on academic titles sourced from three major academic databases (Web of Science, Scopus and ProQuest), with additional support from Google Scholar. A significant post-2020 increase in academic title studies illustrates the growing importance of effective title formulation in the digital age of academia. The review indicated a geographical concentration of studies from the regions of Asia and Europe, highlighting a gap in contributions from other regions like North and South America, and Africa. It also revealed a prevalent focus on the research contents of titles‟ length, syntactic structure, and information attribute, alongside an emphasis on cross-disciplinary comparisons, particularly between titles from „hard‟ and „soft‟ sciences. This review not only mapped the current landscape of academic title research in genre analysis but also suggested potential directions for further exploration, aiming to enhance a more comprehensive and globally representative understanding of this crucial aspect of academic communication.